Implementasi Pengelolaan Kelas Dalam Pembelajaran Pai (Studi Kasus Di Mi. Al Munir Gadungan Puncu Kediri) - Imam khowim (JURNAL ILMIAH INNOVATIVE (Jurnal Pemikiran Dan Penelitian), 2024)
This research is motivated by the teacher's efforts in classroom management which is very necessary in the learning process, because the teacher's efforts in classroom management can create a conducive learning environment so that learning objectives are achieved effectively and efficiently. If the learning process is effective and efficient, it will increase students' interest in learning so that students understand more about the material presented and have an impact on increasing learning achievement. The focus of the research in writing this thesis is (1) How is the implementation of classroom management in cognitive learning achievement of students at MI Al Munir Gadungan Puncu Kediri? (2) How is the implementation of classroom management in the affective learning achievement of students at MI Al Munir Gadungan Puncu Kediri? (3) How is the implementation of classroom management in psychomotor learning achievement of students at MI Al Munir Gadungan Puncu Kediri? This study uses a qualitative approach with descriptive research type, the research location is in MI. Al Munir Gadungan Puncu Kediri, the data source is obtained through 3 elements, namely primary data and secondary data, the data collection method uses observation, interviews and documentation. In analyzing the data using descriptive analysis techniques, while checking the validity of the data using extended observations or researcher participation, increased persistence or constancy of observers, and triangulation. The results of this study are: (1) in the learning process of fiqh teachers at MI. Al Munir Gadungan Puncu Kediri Teachers in improving the ability of students in learning, usually teachers use the evaluation stage, namely, written and oral evaluation. Not only by using evaluation, usually the teacher also holds presentations and daily tests. (2) the affective behavior carried out by the fiqh teacher is by forming the attitudes of students not only by focusing on a teacher, but also by parents having a will, because it is parents who understand their students. the formation of attitudes there must be motivation to learn. (3) psychomotor performed by MI teachers. Al Munir Gadungan Puncu Kediri is the learning process of a teacher in teaching students so that it is easy to understand the material, it is necessary to include examples around the environment and learning can be directed according to its objectives.